Frailty mediated the association between tooth loss and mortality in the oldest old individuals: a cohort study - Wang, MingXia; Deng, Xiaomeng; Chen, Hanjie; Diao, Yuhan; Liu, Chang; Gao, Jun; Tang, Xin; Li, Xiaoyan; Liu, Yan; Duan, Jun (Frontiers in Public Health, 2024)
Tooth loss is associated with increased mortality risk; however, the mechanism underlying this is still not clear. The objective of this study was to explore whether frailty mediates the association between tooth loss and mortality risk among the oldest old individuals. The participants were followed up from 1998 to 2018 in the Chinese Longitudinal Healthy Longevity Survey (CLHLS). Frailty was constructed following a standard procedure. The mortality, frailty, and the tooth loss were applied as the outcome, mediator, and independent variable, respectively. The Cox model was fitted, including possible confounders, for causal mediation analysis. A total effect (TE), an average causal mediation effect (ACME), an average direct effect (ADE) and a proportion mediated (PM) were calculated. During 129936 person-years at risk, 31899 individuals with mean age 91.79 y were included. The TE and ADE of severe tooth loss on mortality were 0.12 (95%CI: 0.08, 0.15) and 0.09 (95 %CI: 0.05, 0.13); the ACME of frailty was 0.03 (95%CI: 0.02, 0.03) with 21.56 % of the TE being mediated. This work illustrated that tooth loss is associated with mortality and frailty appeared to mediate the relationship.